A critical race theory test of W.E.B. DuBois' hypothesis: Do Black students need separate schools?. Issue 3 (16th April 2022) - Yosso, Tara J.; Smith, William A.; Solórzano, Daniel G.; Hung, Man
ABSTRACT: Guided by a critical race theory framework, this study tested W.E.B. DuBois' hypothesis that Black students need not attend integrated schools to succeed academically. DuBois offered this controversial hypothesis nineteen years before Brown v Board of Education, in his 1935 essay, "Does the Negro Need Separate Schools?" His concern focused on the hostility and aversion toward Blacks evident in integrated school settings. In the landmark Brown case, the integration rationale successfully convinced the Court to rule for desegregating schools. However, it also positioned Black students as the source of the problem instead of the racially unequal distribution of educational resources. Unfortunately, instead of finding a remedy for inferior schooling conditions, U.S. Supreme Court decisions on school desegregation, such as Seattle/Louisville (2007), continue to perpetuate this troubling message. We analyzed African American students' math achievement scores from the Early Childhood Longitudinal Study to test DuBois' hypothesis and challenge the underlying inferences of the integration rationale. In our discussion of the study findings, we also considered the need to redefine the racial ''tipping point'' in schools.